2007
DOI: 10.5194/acp-7-973-2007
|View full text |Cite
|
Sign up to set email alerts
|

Mirror image hydrocarbons from Tropical and Boreal forests

Abstract: Abstract. Monoterpenes, emitted in large quantities by trees to attract pollinators and repel herbivores, can exist in mirror image forms called enantiomers. In this study such enantiomeric pairs have been measured in ambient air over extensive forest ecosystems in South America and northern Europe. For the dominant monoterpene, α-pinene, the (−)-form was measured in large excess over the (+)-form over the Tropical rainforest, whereas the reverse was observed over the Boreal forest. Interestingly, over the Tro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 39 publications
3
52
0
Order By: Relevance
“…This could partly explain the diurnal pattern of α-pinene mixing ratios, which exhibit some relation to a light-and temperature-dependent emission flux (Kuhn et al, 2002;Rinne et al, 2002;Williams et al, 2007). However, this behaviour was not observed for all monoterpene species.…”
Section: Compoundmentioning
confidence: 84%
“…This could partly explain the diurnal pattern of α-pinene mixing ratios, which exhibit some relation to a light-and temperature-dependent emission flux (Kuhn et al, 2002;Rinne et al, 2002;Williams et al, 2007). However, this behaviour was not observed for all monoterpene species.…”
Section: Compoundmentioning
confidence: 84%
“…Ozone formation in inlet lines or on the fuselage of aircrafts has been documented to lead to measurement artefacts (Ridley et al, 2006, and references therein) whereas experimental evidence for ozone production by electrical discharges in the free troposphere is inconclusive. Shlanta and Moore (1972), Winterrath et al (1999) and Zahn et al (2002) suggested direct ozone production from corona discharge to explain the observed enhanced mixing ratios in a thunderstorm cloud and convectively active areas, respectively. In these studies no yield of O 3 molecules per flash is given.…”
Section: Missing Ozone Sourcementioning
confidence: 96%
“…Table 1 shows an overview of the various measured species and the related measurement techniques that were applied for the different instruments for the GABRIEL campaign. Further information of the measured species is reported in Stickler et al (2007), Williams et al (2007), Gebhardt et al (2008), Eerdekens et al (2009) and Martinez et al (2010). In 10 measurement flights, of 3 to 3.5 h each, the troposphere was probed in a region between 3.5 and 6 • N and between 59 and 51 • W .…”
Section: Mission Descriptionmentioning
confidence: 99%
“…To date, little work has been done to analyze naturally occurring enantiomeric gas phase biogenic emissions. Specific plant emissions have been investigated previously using a β-cyclodextrin capillary GC with charcoal adsorption/solvent extraction (Yassaa et al, 2000), and carbograph adsorption/thermal desorption (Yassaa et al, 2001;Williams et al, 2007). In our previous works, we have reported on the applicability of SPME for qualitative study of the biogenic emission of enantiomeric and nonenantiomeric monoterpenes from living plants (Yassaa andWilliams, 2005, 2007).…”
Section: Introductionmentioning
confidence: 99%